"Nothing about Us without Us" Meets the "All Teach, All Learn" Model: Autistic Self-Advocates as Leaders and Collaborators in Project ECHO - Karís A. Casagrande; Sage Davis; Benjamin S. Moore; Angela V. Dahiya; Ivanova Smith; Sydney Krebsbach; James Mancini (MDPI AG, 2024)
Those with intellectual and developmental disabilities (I/DD), especially autism, represent an often misunderstood and underserved population. In order to address health disparities faced by those with I/DD in Washington state, the Extension for Community Healthcare Outcomes (Project ECHO) model was implemented to build capacity to serve these individuals and their families in their home communities. Through this year-long telementorship and learning community, expert teams lead clinics based on interdisciplinary case-based discussion and knowledge sharing with medical, behavioral, and mental healthcare providers. A cornerstone of these expert teams are autistic self-advocates, who provide insight into lived experience. In this paper, we will discuss how the inclusion of six autistic self-advocates across four different ECHO programs has allowed ECHO participants to broaden their horizons and gain new insight into supports for their I/DD clients across multiple aspects of care. In addition to the unique knowledge provided by self-advocates, their participation illustrates the potential for all people with I/DD to live rich and fulfilling lives. The initial implementation and on-going success of including lived experience within the ECHO model can be used as an example of how to create partnerships that meaningfully inform decisions and improve equitable outcomes in service provision.